2021
DOI: 10.1038/s41598-021-91109-2
|View full text |Cite
|
Sign up to set email alerts
|

Biochip with multi-planar electrodes geometry for differentiation of non-spherical bioparticles in a microchannel

Abstract: A biosensor capable of differentiating cells or other microparticles based on morphology finds significant biomedical applications. Examples may include morphological determination in the cellular division process, differentiation of bacterial cells, and cellular morphological variation in inflammation and cancer etc. Here, we present a novel integrated multi-planar microelectrodes geometry design that can distinguish a non-spherical individual particle flowing along a microchannel based on its electrical sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Because the characteristics of cells in different frequency ranges are different, studies have shown that the excitation frequency is usually more sensitive to cell size when the excitation frequency is around 0.5 MHz. , To ensure that the output signal has a sufficiently high SNR, the frequency of the excitation signal in this experiment was set to 500 kHz. In addition, the typical sample concentration in the experiment was around 10 5 particles/mL, a syringe pump (LSP01-1B, Baoding Longer Precision Pump Co., Ltd.) was set at 1.2 μL/min for fluidic control, and the speed of the cells in the microchannel was about 0.01–0.04 m/s.…”
Section: Resultsmentioning
confidence: 99%
“…Because the characteristics of cells in different frequency ranges are different, studies have shown that the excitation frequency is usually more sensitive to cell size when the excitation frequency is around 0.5 MHz. , To ensure that the output signal has a sufficiently high SNR, the frequency of the excitation signal in this experiment was set to 500 kHz. In addition, the typical sample concentration in the experiment was around 10 5 particles/mL, a syringe pump (LSP01-1B, Baoding Longer Precision Pump Co., Ltd.) was set at 1.2 μL/min for fluidic control, and the speed of the cells in the microchannel was about 0.01–0.04 m/s.…”
Section: Resultsmentioning
confidence: 99%
“…Platinum electrodes were assigned a relative permittivity of 7 (ε r ) and electrical conductivity of 8.9 × 10 6 S/m. Similar material properties were used in our earlier simulation studies as well. , …”
Section: Methodsmentioning
confidence: 99%
“…Similar material properties were used in our earlier simulation studies as well. 21,22 Blood Sample Acquisition. De-identified biological samples for device testing were obtained from the blood pathology lab at Robert Wood Johnson University Hospital.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…To overcome this limitation, Morgan and Spencer proposed a novel multi-planar electrode design for morphological discrimination of non-spherical cells and bioparticles using multiple frequency impedance measurements in a narrow microchannel region, referred to as a microfluidic constriction channel system. 74 The constriction channel design refers to an impedance flow cytometry system containing a narrow region, a relaxing region, and a pair of electrodes. [75][76][77][78][79] The narrow region has dimensions smaller than that of cells.…”
Section: Electrode Engineeringmentioning
confidence: 99%
“…To overcome this limitation, Morgan and Spencer proposed a novel multi-planar electrode design for morphological discrimination of non-spherical cells and bioparticles using multiple frequency impedance measurements in a narrow microchannel region, referred to as a microfluidic constriction channel system. 74…”
Section: Bioengineering Approaches For Cell Analysismentioning
confidence: 99%